Determining the drivers of long-term aridity variability: a southern African case study - (:unkn) unknown (My University, 2016)
This paper highlights the importance of differentiating between precipitation amount and moisture availability ('humidity'/'aridity') when considering proxy records of climate change. While the terms are sometimes used interchangeably, moisture availability is determined by both (i) precipitation amount and (ii) temperature, through its influence on potential evapotranspiration. As many palaeoenvironmental proxies reflect changes in this water balance rather than purely precipitation amount, it is important to distinguish between the potential relative influences of precipitation and temperature if those records are to be interpreted in terms of climate mechanisms and/or compared with model outputs. As a case study, we explore how precipitation and temperature have determined moisture availability in South Africa's summer rainfall zone over the last 45 000 years. Using quantitative reconstructions of mean annual temperature, summer rainfall amount and an aridity index, our analysis reveals strong spatiotemporal variability in the relative influences of precipitation and temperature on aridity. Temperature is shown to have exerted a considerable and even dominant influence on moisture availability, resulting in elevated humidity during the last glacial period, despite significant reductions in precipitation amount.
Keywords: African Research